Investigation of Surface Soil Contamination around the Qayen Cement Factory by Lead and Chromium - Mohammad Hossein Sayadi; Mohammad Reza Rezaei; Mahmoud Hajiani (محیط زیست و مهندسی آب, 2018)
Heavy metals are a global problem; their entrance to the human food chain bring about irreparable problems. These metals are naturally occurring in rocks and soils, but the release of metals into the soil has increased through human activity over the past decade. The purpose of this study was to determine the contamination of heavy metals like, lead and chromium in the soil around the Qayen Cement Plant using the geo-accumulation index, pollution factor and pollution index. According to a systematically sampled network at eight different directions in distances of 200, 300, 400, 500, 600, 700, 800 and 1000 meters from the cement factory, totally, 64 samples were taken. Soil samples were passed through a 2-mm sieve, and then digested with hydrofluoric acid, perchloric acid, hydrochloric acid, and nitric acid then the concentration of Pb and Cr was measured using atomic absorption spectrometer (Contr AA700) through flame method. The results suggest that the average metal chromium and lead were 52.05 and 66.79 mg/kg respectively. A Geo-accumulation index value for the metal in all stations at various distances is located in classes I and II (non-polluted to little contaminate). Pollution index values indicate that the stations at various distances, the moderate pollution accounted for 39 and 44% chromium and lead, as well as high pollution as 61 and 56% of these two elements respectively. In conclusion, as the result shows the concentration of Pb and Cr are higher than control samples and are accumulating.